1988
DOI: 10.1002/aic.690340906
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative simulation of chemical process systems: Steady‐state analysis

Abstract: A method of qualitative simulation for continuous process systems that predicts the steady-state measurement patterns generated as a result of process malfunctions is presented. The method is based on qualitative versions of the steady-state process equations and requires no numerical information beyond the signs and relative values of certain groups of parameters. Previous methods of qualitative simulation (Umeda et al., 1980; de Kleer and Brown, 1984;Forbus, 1984;Kuipers, 1986) have tended to generate multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 18 publications
1
109
0
Order By: Relevance
“…Its theoretical basis is nodal balance [48]. A depth-first traversal algorithm constructs a path by moving each time to an adjacent node until no further arcs can be found that have not yet been visited, the implementation of which is a recursive procedure.…”
Section: Graph Traversalmentioning
confidence: 99%
“…Its theoretical basis is nodal balance [48]. A depth-first traversal algorithm constructs a path by moving each time to an adjacent node until no further arcs can be found that have not yet been visited, the implementation of which is a recursive procedure.…”
Section: Graph Traversalmentioning
confidence: 99%
“…Because there may be multiple perfect matchings between equations and variables, the corresponding SDGs may not be unique. Some treatment should be made to screen the unsteady or spurious SDGs (Oyeleye & Kramer, 1988;Maurya et al, 2003a). For example, a tank system is shown as Fig.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The basis of the qualitative simulation in CATS was laid down by the Massachusetts Institute of Technology [3] [4]. There, a tool was needed to describe process malfunctions of large systems in chemical engineering.…”
Section: Introductionmentioning
confidence: 99%